Rhyme stew - Dahl, Roald; Blake, Quentin (London : Cape, 1989)
An illustrated collection of fifteen parodies ranging from skewered nursery rhymes to epic slapstick sagas.
"First published 1989. Reprinted 1989"--P. [4].
Keywords: English poetry; Parodies; English poetry; Nonsense verses